Face Skin Detector / Fatin Azirah Mohd Shukor, Fatin Farhana Awang and Nur Liyana Samshir - Mohd Shukor, Fatin Azirah; Awang, Fatin Farhana; Samshir, Nur Liyana (2018)
Our team is planning to develop a face skin detector which consists of modern technologies such as diode laser system and analysis software system. Both of the system functioning in scanning, detect the skin problems, recommend skincare products and also have printing function. The idea is generated from reading a newspaper article from PR Newswire (01 August 2017) reported that about 65 percent of consumers in United States have no idea about the ingredients in the facial cleanser and 63 percent do not understand the purpose of those ingredients which lead to face skin problem. This product is convenient as it needed to put on a table and no need to carry anywhere. A survey conducted among 112 respondents of age between 20-28 years old, the results shows that they wanted to try the automatic face skin detector if it is available in market. The respondents include men and women. The concept will be tested among 20 people to predict sales and profits from the face skin detector. Once the product is ready, it will be test at the market.